(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study investigated the determinants of malaria infection among mothers with under-five children in State Specialist Hospital, Ikere - Ekiti, Ekiti State. The research focused on assessing mothers’ knowledge of malaria infection among under-five children, exploring their perceptions of malaria infection in this age group, and examining the determinants contributing to malaria infection in this specific population. A descriptive survey research design was employed, and data were collected from 217 mothers attending the Child Welfare Clinic through convenience sampling. A questionnaire named "Determinants of Malaria Infection Questionnaire" (DMIQ) was used for data collection, which underwent validation and reliability testing. Descriptive statistics were employed for data analysis, including frequency counts, percentages, mean, and standard deviation. The findings revealed varying levels of knowledge and perceptions among mothers regarding malaria in under-five children, highlighting areas for potential improvement in malaria education and awareness campaigns. It was recommended among others that nurses should implement targeted educational programs and awareness campaigns aimed at mothers to improve their knowledge about malaria infection among under-five children. These campaigns should cover topics such as malaria causes, transmission, symptoms, and preventive measures. Special emphasis should be placed on correcting misconceptions, such as the belief that antibiotics can cure malaria.